Aquatic bird communities in Andean lakes of Ecuador are increasingly dissimilar over time. (February 2021) - Guevara, Esteban A.; Santander G., Tatiana; Espinosa, Rodrigo; Graham, Catherine H.
Highlights: We study changes in community composition of aquatic birds at Andean lakes. Population growth of dominant species influenced community composition. High eutrophication at multiple lakes likely benefitted dominant species. Abstract: Andean lakes are important for human well-being and biodiversity conservation, yet human-induced environmental changes threaten their biodiversity and the ecosystem services they provide. Knowledge of the relationship between biodiversity and environmental factors can provide insight into how human activity impacts lakes. We report trends of community composition of aquatic bird communities at six Andean lakes in Ecuador based on 15-years of monitoring. Additionally, we explore relationships among the abundance of aquatic bird species and environmental variables, such as elevation, water depth, biochemical demand of oxygen and concentration of phosphates and nitrites. We found a sustained population growth of one species of herbivorous bird, the Andean Coot, Fulica ardesiaca, across all lakes . Local trends in community composition show directional changes in four lakes and were likely a result of abundance increases of this species. Environmental factors related to eutrophication explained the abundance of F. ardesiaca, indicating that ongoing eutrophication of Andean Ecuadorian lakes, which results in increased submerged vegetation, benefits herbivorous species like this. Management measures that prevent further eutrophication combined with on-going monitoring should be considered in order to maintain ecosystem health and functioning.